Biological Roles and Delivery Strategies for Ions to Promote Osteogenic Induction - Bosch-Rué, Elia; Diez-Tercero, Leire; Giordano-Kelhoffer, Barbara; Delgado, Luis M.; Bosch, Begoña M.; Hoyos-Nogués, Mireia; Mateos-Timoneda, Miguel Angel; Tran, Phong A.; Gil, Francisco Javier; Perez, Roman A. (Frontiers in Cell and Developmental Biology, 2021)
Bone is the most studied tissue in the field of tissue regeneration. Even though it has intrinsic capability to regenerate upon injury, several pathologies and injuries could hamper the highly orchestrated bone formation and resorption process. Bone tissue engineering seeks to mimic the extracellular matrix of the tissue and the different biochemical pathways that lead to successful regeneration. For many years, the use of extrinsic factors (i.e. growth factors and drugs) to modulate these biological processes have been the preferred choice in the field. Even though it has been successful in some instances, this approach presents several drawbacks, such as safety-concerns, short release profile and half-time life of the compounds. On the other hand, the use of inorganic ions has attracted significant attention due to their therapeutic effects, stability and lower biological risks. Biomaterials play a key role in such strategies where they serve as a substrate for the incorporation and release of the ions. In this review, the methodologies used to incorporate ions in biomaterials is presented, highlighting the osteogenic properties of such ions and the roles of biomaterials in controlling their release.